Understanding Impact of Information System Quality on Software as a Service: An Empirical Study - Hariguna, Taqwa; Lai, Min Tsai; Chen, Shih Chih (International Journal of Information Studies, 2025)
Cloud computing specially on Software as a Service (SaaS) is currently powerful instrument and has attracted substantial attention from industrial, practitioners and academics. This paper aimed to develop an integrated model designed to predict, to examine and to understand information system quality on Software as a Service during the formation of sustainable of continuous intention of customers in cloud computing contexts. The participants were from 144 samples, most of respondents were CIOs and CEOs. Structural equation modeling was applied to demonstrate the stability of the proposed model and the results of hypotheses testing. The analysis results demonstrated that customers’ continuous intention and customers’ satisfaction were determined significantly by SaaS Quality. Satisfaction was also the significant motivator of customers’ continuous intention. The differences among various types of SaaS application were not analyzed. This study suggests that future studies should extend research including users of various SaaS applications such as office application software, enterprise resource plan, customer relationship management system and so on. This paper proposed a comprehensive model to synthesize the essence of SaaS quality for explaining customers’ satisfaction and customers’ continuous intention of SaaS.